EUREFE’17 International Conference - KÜÇÜKKAYA, Hatice (Turkish Economic Review, 2017)
Abstract. The 2nd International Conference EUREFE (EUREFE’17) was held on 27-29 July 2017, in Aydin. This year’s conference theme was about ‘Economic, Administrative and Political Transformations in the World and Turkey: Impacts and Policy Recommendations’. The conference, organized by Aydin Faculty of Economics-Adnan Menderes University, welcomed many scientists and participants from different parts of Turkey and all around the world. Keywords. EUREFE’17, Income inequality, Transition economies, Panel data. JEL. E10, P20, C33.